2016
DOI: 10.5943/mycosphere/7/2/4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and total phenolic content of Volvariella volvacea and Schizophyllum commune mycelia cultured in indigenous liquid media

Abstract: Reyes RG 2016 -Antioxidant activity and total phenolic content of Volvariella volvacea and Schizophyllum commune mycelia cultured in indigenous liquid media. Mycosphere 7(2), 131-138, Doi 10.5943/mycosphere/7/2/4 AbstractIn the current work, we evaluated the different indigenous liquid culture media for mycelial production and antioxidant property based on radical scavenging activity and total phenolic content of Volvariella volvacea and Schizophyllum commune. In V. volvacea culture, the maximum mycelial bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Reactive oxygen species (ROS) represent the most potent free radicals since they can have a destructive effect on various cells and cause oxidative stress [ 1 , 2 ]. The imbalance between the production and quenching of free radicals may lead to a wide range of diseases, including neurodegenerative disorders such as Alzheimer’s (AD) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) represent the most potent free radicals since they can have a destructive effect on various cells and cause oxidative stress [ 1 , 2 ]. The imbalance between the production and quenching of free radicals may lead to a wide range of diseases, including neurodegenerative disorders such as Alzheimer’s (AD) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mbayo et al [ 27 ] reported that methanol extract of T. gibbosa exhibited activity against Pseudomonas aeruginosa , Staphylococcus aureus , Streptococcus pneumoniae , and Shigella sonnei , with MIC values of 1.25, 2.5, 5, and 2.5 mg/mL, respectively. S. commune has long been acknowledged for its medical importance and have been reported to exhibit antioxidant [ 28 ], antitumor and immune-modulating [ 29 ], anti-inflammatory [ 30 , 31 ], and antimicrobial [ 32 ] activities. Acetone and ethyl alcohol extracts of S. commune Fr.…”
Section: Introductionmentioning
confidence: 99%
“…have been reported to exhibit activities against Escherichia coli ATCC 25922, Staphylococcus aureus , and Pseudomonas aeruginosa ATCC 27857 via the agar diffusion method [ 33 ]. V. volvacea is an edible mushroom that has been reported to exhibit antioxidant [ 31 , 34 ], hepatoprotective [ 35 ], anticancer [ 36 , 37 ], immune-modulatory [ 38 ], and antimicrobial [ 39 , 40 ] activities. V. volvacea is reported to exhibit activity against Bacillus subtilis , Proteus vulgaris , and Candida albicans [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of mushrooms including Agaricus bisporus [48] Lentinus edodes [49], Armillaria mellea [50], Auricularia auricula [51], Boletus edulis [52], Ganoderma applanatum [53], Grifola frondosa [54], Hypsizigus marmoreus [55], Pleurotus sp. [56], Schizophyllum commune [57], Termitomyces sp. [58], and Tricholoma sp.…”
Section: Mushrooms As Antioxidantmentioning
confidence: 99%